The Competitive Threat Posed by the People's Republic of China to Latin America: An Analysis for 1990-2002 - Sanjaya Lall; John Weiss (Asian Development Bank Institute (ADBI), 2005)
This paper explores the competitive threat posed by the People's Republic of China to markets in Latin America and the Caribbean (LAC). It focuses on the impact of PRC's rise as a major exporter of manufactures, but it also considers bilateral trade between LAC and PRC. In response to falling trade costs and greater international capital mobility, PRC has emerged as a major exporter at both the labor-intensive low technology and increasingly at the knowledge-intensive higher technology end of the product spectrum. Latin America is still somewhat distant from this process. Some countries are benefiting from growing imports of primary and resource-based products by PRC, although in general PRC remains a relatively small market for LAC, although as an import supplier PRC overtook Japan in 2003. The trade structure of most of LAC is generally more complementary than competitive with that of PRC. The exceptions are principally Mexico and Costa Rica, which, similar to PRC, are closely integrated into production networks of MNCs. With a differing export structure the likelihood of damaging trade diversion effects is weakened. Our analysis of bilateral trade between LAC and PRC reveals a striking tendency towards a pattern of specialization with LAC a net exporter of primary products and a net importer of manufactures. The patterns of the two regions are almost a classic textbook illustration of trade between developing and industrialized regions, where the former (i.e. LAC) strengthens its specialization in primary products and processes resources while the latter (i.e. PRC) does the reverse. What is surprising is that LAC is the richer region, with a longer history of modern industrialization, higher human resources, more FDI per capita and with more liberal trade and investment regimes. The original version of this paper was prepared for the CDRF/ADBI/IDB First LAEBA Annual Conference on `The Emergence of China: Challenges and Opportunities for Latin America and Asia' held in Beijing on 3-4 December 2004.
hdl:11540/4170
Keywords: 330